Menuju Teologi Identitas: Kajian atas Rekonstruksi dan Representasi Moral Kristen Barat terhadap Makna Mu’kur di Minahasa - Denni H. R. Pinontoan (Indonesian Journal of Theology, 2015)
In this article, I argue that issues, particularly with regard to concerns of "life after death" and the role of Minahasan forebears within the life of the community, have over time been shaped, reconstructed, and re-represented by a Western Christian moralism. A counterproposal is offered, in the form of a "theology of identity." Embracing an understanding of identity as being a summative projection of a "newborn spirit," this emerging approach to theologizing Minahasan identity offers a novel means to attend to certain turmoils that have festered within the life of the Minahasan church and its Christians.